GATED COMMUNITIES IN COSTA RICA: A NEW OBJECT OF STUDY - Alvarado Alcázar, Alejandro (2013)
The intense application of neoliberal model in all Latin America since the 80th, has brought with it great transformations on its social structures with an evident space expression in the city, among them, the rise of gated communities as a real estate milestone of the elite in countries of region. This article presents the study of the state of this new urban form in Costa Rica and the impacts they have had on the open community.